Extra-lessons: A comparison between "different sides of the track" in Trinidad and Tobago - Lochan, Samuel; Barrow, Dorian (School of Education, UWI, St. Augustine, 2008)
This paper attempts to compare the participation in extra-lessons by the students of a senior comprehensive school and a traditional seven -year girls' school in Trinidad and Tobago. Survey data were gathered from 25 students at each level from Forms 4, 5, and 6 in each school. Data are presented on the socio-economic status of different students, participation rates by students of the two schools, subjects chosen by students for extra-lessons, costs per subject, reasons for seeking extra-lessons, and the effects of extra-lessons. This study therefore presents some data on private lessons not previously available. It also draws some comparisons between the two schools that are critical for understanding school performance in Trinidad and Tobago
Keywords: Secondary school students; Extra-lessons; Sociology of education; Participation rate; Public schools; Assisted schools; Denominational schools; Comparative analysis; Trinidad and Tobago